2006
DOI: 10.1097/01.mpg.0000256243.02677.59
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine Maintains First Remission in Newly Diagnosed Pediatric Crohn's Disease

Abstract: 6-Mercaptopurine (6-MP) maintains remission in pediatric Crohn's disease (CD). Azathioprine, a prodrug of 6-MP, is used for maintenance of remission of CD in Europe. We evaluated to what extent azathioprine is used in newly diagnosed pediatric CD patients and whether maintenance of remission differed between patients using azathioprine or not. Charts of children (diagnosed 1998Y2003, follow-up Q 18 mo) were reviewed. Active disease was defined as Pediatric Crohn's Disease Activity Index (PCDAI) greater than 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(24 reference statements)
0
8
1
Order By: Relevance
“…Pediatric studies have shown the efficacy of immunomodulators (6-mercaptopurine, azathioprine, and methotrexate) in maintaining remission in pediatric CD (33)(34)(35)(36).…”
Section: Cd-specific Therapiesmentioning
confidence: 99%
“…Pediatric studies have shown the efficacy of immunomodulators (6-mercaptopurine, azathioprine, and methotrexate) in maintaining remission in pediatric CD (33)(34)(35)(36).…”
Section: Cd-specific Therapiesmentioning
confidence: 99%
“…Early commencement of TP, within 6 months of diagnosis, has become widespread practice in both adult and pediatric CD since a seminal RCT in treatment naïve children with CD demonstrated a greater steroid-free remission in those commenced on early thiopurines [8]. Recent retrospective pediatric studies have reported much lower efficacy of TP in maintaining remission in pediatric CD [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In studies without early IMM use, the remission rates seemed to be higher when EEN was used as induction treatment (Fig. 4 in ''Appendix,'' column 2, 3) [15,32,33]. Contrary to CS, positive impact of EEN on mucosal healing may potentially increase durability of remission [6,9].…”
Section: Discussionmentioning
confidence: 80%
“…Several recently published studies comparing long-term outcomes of EEN and CS have assessed and compared rates of remission between groups (Fig. 4 in ''Appendix'') [15][16][17][18][19][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation